Vascular Access in Neonates and Children - Biasucci, Daniele G.; Disma, Nicola Massimo; Pittiruti, Mauro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This is a practical guide to pediatric vascular access. It covers how to use ultrasound appropriately, how to prevent and manage early and late complications, and how to correctly place the catheter tip using ECG or radiology. It includes all the most modern approaches and devices. In particular, the best approach for some specific populations is covered, including neonates and infants, complex patients, and children with cancer or renal failure requiring long term treatments. A guide on how to establish a vascular access team in a pediatric hospital is included, including the costs and benefits of having this hospital-based team. Vascular Access in Neonates and Children is aimed at pediatric anesthesists and surgeons, and radiologists, pediatricians and other specialities may also find it of interest.
Part 1: General considerations on venous access in neonates and children -- Chapter 1: Vascular access in pediatric patients: classification and indications -- Chapter 2: Evidence based rationale for ultrasound guided vascular access in children -- Chapter 3: Principles of ultrasonography and settings of ultrasound devices for children -- Chapter 4: Ultrasound anatomy of arterial and deep veins of the limb and the cervico-thoracic region in children -- Chapter 5: Near-InfraRed technology for access to superficial veins: evidence from the literature and indications for pediatric venous access -- Chapter 6: Tip navigation and tip location methods -- Chapter 7: Chest ultrasound for early diagnosis of complications -- Chapter 8: Technique and devices for securement of the catheter and protection of the exit site -- Part 2: Venous access in neonates -- Chapter 9: Peripheral venous access in neonates -- Chapter 10: Umbilical venous catheters -- Chapter 11: Epicutaneo-cava catheters -- Chapter 12: Ultrasound guided venous access in neonates -- Part 3: Venous access in children -- Chapter 13: Peripheral venous access: short cannulas, mini-midlines, midlines -- Chapter 14: Peripherally Inserted Central Catheters (PICC) in children -- Chapter 15: Centrally and Femorally Inserted Central Catheters (CICC and FICC) in children -- Chapter 16: Totally Implantable Venous Access Devices -- Part 4: Arterial access -- Chapter 17: Umbilical arterial catheters -- Chapter 18: Peripheral arterial lines -- Part 5: Special considerations in pediatric vascular access -- Chapter 19: Access for dialysis and apheresis -- Chapter 20: Intraosseous Access -- Chapter 21: Prevention and treatment of catheter-related complications -- Chapter 22: Compatibility of drugs -- Chapter 23: Organization of a hospital-based Vascular Access Team -- Chapter 24: Special problems of venous access in intensive care and emergency -- Chapter 25: Special problems of venous access in oncology and hematology -- Chapter 26: Special problems of venous access in parenteral nutrition -- Chapter 27: Sedation and general anesthesia for vascular access in children.
Keywords: Anesthesiology; Pediatrics; Surgery; Radiology; Anesthesiology; Pediatrics; Surgery; Surgery; Radiology; Arteriovenous Malformations; Child; Infant